The Relationship between Thoracic Trauma Scoring and Mortality in Blunt Thoracic Trauma Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Ahmat Umar; Marrantiza, Satria; Theodorus (Sriwijaya Journal of Surgery, 2023)
Introduction: Closed thoracic trauma is frequently associated with rib fractures and pulmonary contusions. Thoracic trauma can be life-threatening if it is not treated immediately and properly. This study aimed to determine the relationship between thoracic trauma scoring and mortality in blunt thoracic trauma patients in sub-population Indonesia, especially at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This study is a cross-sectional observational study. A total of 70 research subjects participated in this study. Data analysis was carried out using SPSS in univariate and bivariate to determine the relationship between thoracic trauma scoring and mortality. Results: There is a significant relationship between CTS scores and mortality (p = 0.000). Patients with a CTS score ≥ 5 were significantly more at risk of dying than patients with a CTS score < 5 (p = 0.000). Conclusion: There is a relationship between CTS score and blunt trauma patient mortality thorax at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.